Strategic framework for selecting advanced air defence systems: insights from a developing country: A Hybrid MCDM Framework for Missile Systems Selection - Ali, Yousaf (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/Purpose: In this modern world, every country is trying to improve its defense system by acquiring new technologies. One of the main components of a defense system is the Air Defense System (ADS), which further includes fighter aircraft, drones, 3D radar, fighter command vehicles, and missile systems. The missile system has become the most important component of air defense systems around the globe. Due to the limited resources and weak economy, it is a challenge for a developing country to acquire an ADS that suits its resources and economic capabilities. This research paper aims to study the needs and goals of the defense system of the Pakistan Air Force (PAF) and to select the best missile system to improve its existing air defense system. Methods: A hybrid Multi-Criteria Decision Making (MCDM) methodology, Decision-Making Trial and Evaluation Laboratory (DEMATEL), and Analytical Hierarchy Process (AHP) are used to evaluate the factors affecting the missile system as well as to select the best missile system for Pakistan. Results: The results depict that the S-400 missile system is the most feasible for Pakistan’s air defense, followed by THAAD and S-300, which can meet the country’s current security needs.Conclusion: The research concludes that precision target capability, range, and maneuverability are the prominent factors that play a greater role in the ADS sector of Pakistan. This research is the first of its kind to use the DEMATEL-AHP approach for the evaluation of air defense systems in the case of a developing country such as Pakistan.